Emerging Role of Platelet-Endothelium Interactions in the Pathogenesis of Severe SARS-CoV-2 Infection-Associated Myocardial Injury - Rossouw, Theresa M.; Anderson, Ronald; Manga, Pravin; Feldman, Charles (Frontiers in Immunology, 2022)
Cardiovascular dysfunction and disease are common and frequently fatal complications of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Indeed, from early on during the SARS-CoV-2 virus pandemic it was recognized that cardiac complications may occur, even in patients with no underlying cardiac disorders, as part of the acute infection, and that these were associated with more severe disease and increased morbidity and mortality. The most common cardiac complication is acute cardiac injury, defined by significant elevation of cardiac troponins. The potential mechanisms of cardiovascular complications include direct viral myocardial injury, systemic inflammation induced by the virus, sepsis, arrhythmia, myocardial oxygen supply-demand mismatch, electrolyte abnormalities, and hypercoagulability. This review is focused on the prevalence, risk factors and clinical course of COVID-19-related myocardial injury, as well as on current data with regard to disease pathogenesis, specifically the interaction of platelets with the vascular endothelium. The latter section includes consideration of the role of SARS-CoV-2 proteins in triggering development of a generalized endotheliitis that, in turn, drives intense activation of platelets. Most prominently, SARS-CoV-2-induced endotheliitis involves interaction of the viral spike protein with endothelial angiotensin-converting enzyme 2 (ACE2) together with alternative mechanisms that involve the nucleocapsid and viroporin. In addition, the mechanisms by which activated platelets intensify endothelial activation and dysfunction, seemingly driven by release of the platelet-derived calcium-binding proteins, SA100A8 and SA100A9, are described. These events create a SARS-CoV-2-driven cycle of intravascular inflammation and coagulation, which contributes significantly to a poor clinical outcome in patients with severe disease.